Children of the Earth. no.13 (Spring, 1986) - (:unkn) unknown (Children of the Earth, 1986)
It's Been a Long Time … -- Other Resources for Pagan Families -- You Know You Have a Pagan Child When -- Rhymes: Row, Row, Row Your Boat ; Ask the Moon When She is Round -- Some Recipes from Brigid & Pixie's Kitchen: Fried Apples ; Oatmeal Cake ; Boiled Topping -- "My Sister Wears the Crown of Lights at Candlemas" / art by Jossy (6) -- Bringing Up a Child in a Pagan Way / by Nicola Miles, Pipes of Pan -- Child's World / poem by Joyce Baker
1 Electronic record(s). 5913915 bytes. 9 pages. CotE_v04n13_1986.pdf
Keywords: Children of the Earth (Newsletter); Neopagan families; Child rearing--Religious aspects--Neopaganism; Child rearing--Religious aspects--Wicca; Neopagan children--Education; Pregnancy--Religious aspects; Liedloff, Jean. Continuum concept; Children’s art; Cooking (Apples)--Recipes; Cooking (Oats)--Recipes; Cooking (Dessert toppings)--Recipes; Imaginary companions--Poetry; Nursery rhymes; Poetry; Recipes; Newsletters